2020
DOI: 10.3390/su12166308
|View full text |Cite
|
Sign up to set email alerts
|

Employer Ratings through Crowdsourcing on Social Media: An Examination of U.S. Fortune 500 Companies

Abstract: The aims of this study are to examine the effect of crowdsourced employer ratings and employee recommendations of an employer as an employer of choice, to examine which employer ratings that represent different employee value propositions can predict the overall employer rating through crowdsourcing, to examine whether the Fortune 500 ranking can also influence overall employer ratings, and to mine which keywords are popularly used when employees post a comment about the pros and cons of their employers on a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…Hence, full mediation has been proved because paths A and B were significant and path C was insignificant. Crowdsourcing fully mediates the positive and significant relationship between restructuring and employer branding, which is consistent with previous research ( Kashive et al, 2020 ; Suen et al, 2020 ).…”
Section: Data Analyses and Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, full mediation has been proved because paths A and B were significant and path C was insignificant. Crowdsourcing fully mediates the positive and significant relationship between restructuring and employer branding, which is consistent with previous research ( Kashive et al, 2020 ; Suen et al, 2020 ).…”
Section: Data Analyses and Resultssupporting
confidence: 91%
“…But external job candidates can only rely on social media word of mouth from existing workers for information. In such cases, to make it better for employers about what employees feel, encounter, and observe they can understand internal employees’ needs more closely ( Suen et al, 2020 ) and then readjust their restructuring process accordingly. Also, with the development of social sites, many people rely on the opinion of peers and their feedback even on social media platforms like Twitter, Instagram, Facebook, LinkedIn, and YouTube.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Luo et al (2016) and Lee and Kang (2017) both note the usefulness of obtaining employee satisfaction data from Glassdoor ratings. Similarly, Karabarbounis and Pinto (2018) and Suen et al (2020) identified the usefulness of Glassdoor ratings to discern employer branding issues.…”
Section: Methodsmentioning
confidence: 97%
“…The authors believe that given the large number of reviews available, the transparency and availability of these reviews and the trend towards other researchers using them, that this choice was appropriate (Karabarbounis and Pinto, 2018;Lee and Kang, 2017;Luo et al, 2016). Landers et al (2019) and Suen et al (2020) have both noted the efficacy of using crowdsourcing panel data collection, similar to Glassdoor ratings, to obtain employee attitudes.…”
Section: Methodsmentioning
confidence: 99%
“…Limited studies are available that consider the idea of employer branding by harnessing crowdsourcing platforms, namely Glassdoor (Dabirian et al, 2017(Dabirian et al, , 2019Kashive et al, 2020;Suen et al, 2020). Yet, a paucity of literature considers the reviews from job posting websites like Indeed.com and the US banking industry.…”
Section: Social Media and Crowdsourcing Platformsmentioning
confidence: 99%